Indonesia’s South China Sea Policy: The Limits of Hedging - Ajeng Rizqi Rahmanillah; Tiara Putih Bastian; Rizky Ihsan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This paper discusses Indonesia's hedging policies towards China, especially in the South China Sea issue. In line with a free and active foreign policy principle, Indonesia seeks a middle way by establishing cooperation with the United States and China, two major powers with different interests in the South China Sea issue. This research is qualitative research using a case study approach. In this study, I carried out two data collection techniques, namely interviews and literature studies. The political elite decides to hedge within a government, so it is motivated more internally than externally. Hedging is a tactic that demands a low commitment to a country that does not represent friend or foe. However, in line with the increasing competition between the two, Indonesia's hedging strategy may fail due to external pressure to join one side. Therefore, in maximizing the hedging strategy, Indonesia seems to need to increase its defense capabilities to increase its bargaining position and deter threats from external parties